REVIEW ON PHOTOSENSITIZER POTENTIAL OF NATURAL DYES FOR ANTIMICROBIALS USING PHOTODYNAMIC INACTIVATION - Ayu Mulyani; Ika Yuni Astuti; Djalil, Asmiyenti Djaliasrin (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Infectious diseases still threaten human life, with incidents continuing to increase every year. The increase in antibiotic resistance in recent years has been one of the causes. This incident triggered research to find alternative antibacterial therapies. One such alternative therapy is Photodynamic Inactivation (PDI). This paper reviews the application of PDI for treating diseases caused by microorganisms, especially dermatitis, periodontitis, blood transfusions, and foodborne diseases, emphasizing the use of natural dyes as photosensitizers. The source for this article was obtained from several indexed databases, such as the National Center for Biotechnology Information (NCBI), Elsevier, and Google Scholar, from 2002 to 2024. The keywords used included “photodynamic therapy